Editorial Team - Jeffers, Joshua (The Toro Historical Review, 2023)
The Toro Historical Review Volume 14, Issue 2 Editorial and Production Team Christopher Garcia Alexander Gonzalez Shaleyah Haywood Issac Rivera Montse Romero Dr. Joshua J. Jeffers, faculty mentor